2013
DOI: 10.1016/j.parkreldis.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and deep brain stimulation in Parkinson's disease: A systematic review

Abstract: The purpose of this review is to assess the current state of the literature on the topic of deep brain stimulation (DBS) and its effects on swallowing function in Parkinson’s disease (PD). Pubmed, Cochrane review, and web of science searches were completed on all articles addressing DBS that contained a swallowing outcome measure. Outcome measures included the penetration/aspiration scale, pharyngeal transit time, oropharyngeal residue, drooling, aspiration pneumonia, death, hyolaryngeal excursion, epiglottic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 36 publications
1
68
0
2
Order By: Relevance
“…A published systematic review of literature did not find clinically significant improvement or decline in swallowing function related to DBS in people with Parkinson's disease, and the authors identified a need for further investigation [1]. This case along with another report of DBS-induced fixed epiglottis causing airway obstruction [2] underscores the need for further investigation into the effects of disease pathophysiology, DBS electrode placement, and intensity of stimulation on swallowing function.…”
Section: Discussionmentioning
confidence: 92%
“…A published systematic review of literature did not find clinically significant improvement or decline in swallowing function related to DBS in people with Parkinson's disease, and the authors identified a need for further investigation [1]. This case along with another report of DBS-induced fixed epiglottis causing airway obstruction [2] underscores the need for further investigation into the effects of disease pathophysiology, DBS electrode placement, and intensity of stimulation on swallowing function.…”
Section: Discussionmentioning
confidence: 92%
“…In theory, impairments in speech and swallowing could be induced more frequently by STN DBS, due to its proximity to corticobulbar fibers, but the cited meta-analysis and an additional systematic review did not confirm this association 26,63 . Some features of gait, such as anticipatory postural adjustments and freezing of gait, could improve with surgery, but postural instability and falls are less likely to improve, and might, in fact, worsen after DBS 40 .…”
Section: Selection Of the Surgical Targetmentioning
confidence: 97%
“…At present, drug treatment and deep brain stimulation therapy are effective for improving PD patients' limb functions, but improvement of swallowing function is not clear and to date remains controversial. [4][5][6][7][8] In recent years, studies have shown that swallowing therapy machine has some effect on vascular Parkinson syndrome with dysphagia.…”
Section: Introductionmentioning
confidence: 99%